Both Sides of the Story: Communication Ethics in Mediatized Worlds. (18th March 2016) - Eberwein, Tobias; Porlezza, Colin
Abstract : Current transformations in the media landscape are challenging contemporary communication and media ethics in at least 2 ways. First, digitization of the media creates new ethical problems that stimulate calls for a redefinition of the norms and values of public communication. Second, new instruments of web‐based media observation introduce new possibilities for media (self‐)regulation and accountability, thus complementing the initiatives of traditional institutions like press councils. The article retraces those conflicting developments by reference to 2 comparative studies, representing the diverging traditions of conventional communication ethics and media accountability research. In bridging over the conceptual gap between the 2 forms of research, the article develops new perspectives for ethical reflection in the mediatized worlds of the digital age.